Evaluation of Wound Healing and Antibacterial Potential of Greyia radlkoferi Szyszyl. Ethanolic Leaf Extract - Loggenberg, Samantha Rae; Twilley, Danielle; De Canha, Marco Nuno; Meyer, Debra; Mabena, Ephraim Cebisa; Lall, Namrita (Frontiers in Pharmacology, 2022)
Angiogenesis is an essential mechanism in both physiological and pathological functions, such as wound healing and cancer metastasis. Several growth factors mediate angiogenesis, including vascular endothelial growth factor (VEGF) and platelet derived growth factor (PDGF). This study evaluated the potential wound healing activity of Greyia radlkoferi Szyszyl (GR) and its effect on growth factors regulating angiogenesis. The ethanolic leaf extract of GR was evaluated for antibacterial activity against wound associated bacteria; Staphylococcus aureus and Pseudomonas aeruginosa. It exhibited antibacterial activity against two strains of S. aureus (ATCC 25293 and ATCC 6538) displaying a minimum inhibitory concentration (MIC) at 250 and 500 μg/ml, respectively. The antioxidant activity of the extract was investigated for nitric oxide (NO) scavenging activity and showed a fifty percent inhibitory concentration (IC50) of 1266.5 ± 243.95 μg/ml. The extract was further investigated to determine its effect on the proliferation and modulation of growth factors secreted by human keratinocytes (HaCaT). Its effect on wound closure was evaluated using the scratch assay, where non-toxic concentrations were tested, as determined by the antiproliferative assay against HaCat cells (IC50 > 400 μg/ml). Results showed that the extract significantly inhibited wound closure, with a percentage closure of 60.15 ± 1.41% (p < 0.05) and 49.52 ± 1.43% (p < 0.01) at a concentration of 50 and 100 μg/ml, respectively, when compared to the 0.25% Dimethyl sulfoxide vehicle control (65.86 ± 1.12%). Quantification of secreted growth factors from cell-free supernatant, collected from the scratch assay, revealed that the extract significantly decreased the concentration of platelet-derived growth factor (PDGF-AA) at both 50 (p < 0.05) and 100 μg/ml (p < 0.001) (443.08 ± 77.36 and 178.98 ± 36.60 pg/ml) when compared to the 0.25% DMSO vehicle control (538.33 ± 12.64 pg/ml). Therefore, whilst the extract showed antibacterial activity against wound associated bacteria, it did not induce wound healing but rather showed a significant inhibition of wound closure, which was confirmed by the inhibition of PDGF-AA, a major growth factor involved in angiogenesis. Therefore, the GR extract, should be considered for further investigation of anti-angiogenic and anti-metastatic properties against cancer cells.